2022
DOI: 10.3390/app13010458
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Experimental Verification of the Interaction in a Hydraulic Directional Control Valve Spool Pair

Abstract: This study examined the impact of mechanical oscillation on a hydraulic directional control valve. Particular attention was paid to the oscillating movement of the spool of the hydraulic directional control valve resulting from this impact. Different models of fluid and mixed friction were considered. The models analysed accounted for the relative movement of the directional control valve body and the fact that it is kinematically excited by external mechanical oscillations. It was observed that the mixed fric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Since the valve control element (e.g., spool) vibrates, the area of the valve's throttling gap changes, which in the hydraulic system is manifested by pulsation of performance and, consequently, of pressure, with the components of the spectrum of this pulsation corresponding to the components of the vibration spectrum of the excited element. Our investigations and literature studies (Wang et al, 2021;Josifovic et al, 2016;Stosiak et al, 2023) show that the resonant frequencies of hydraulic valve control elements (conical poppets, spools) are below 100 Hz (Stosiak et al, 2023). The range of these frequencies is also particularly dangerous for humans since the resonant frequencies of vital internal organs are also below 100 Hz (Zheng et al, 2019;Arnold et al, 2018;Govindan et al, 2020).…”
Section: Introductionmentioning
confidence: 56%
“…Since the valve control element (e.g., spool) vibrates, the area of the valve's throttling gap changes, which in the hydraulic system is manifested by pulsation of performance and, consequently, of pressure, with the components of the spectrum of this pulsation corresponding to the components of the vibration spectrum of the excited element. Our investigations and literature studies (Wang et al, 2021;Josifovic et al, 2016;Stosiak et al, 2023) show that the resonant frequencies of hydraulic valve control elements (conical poppets, spools) are below 100 Hz (Stosiak et al, 2023). The range of these frequencies is also particularly dangerous for humans since the resonant frequencies of vital internal organs are also below 100 Hz (Zheng et al, 2019;Arnold et al, 2018;Govindan et al, 2020).…”
Section: Introductionmentioning
confidence: 56%
“…The size of the abrasive debris was significantly different. Part of the abrasive debris was newly generated, which indicated that not only abrasive wear but also three-body wear had occurred during wet friction [22]. The end point of partial furrows was visible (the red dashed line) in Figure 10f, which was the result of the abrasive SiC being blocked by the Cr 7 C 3 hard phase and being unable to deflect to the nearby area.…”
Section: Wear Morphologymentioning
confidence: 99%
“…The formation and presence of water films are the result of complex physical and chemical processes between solids and liquids. The water-film thickness is not a fixed value and is affected by many factors such as temperature, pressure, minerals, curvature, and formation water [57]: (1) regarding the effect of temperature, a higher temperature is associated with more intense molecular thermal motion, leading to a smaller water-film thickness. ( 2) Regarding the effect of formation pressure, Wang, W.M.…”
Section: Research Advances In Water-film Thicknessmentioning
confidence: 99%